OTA for WLAN WiFi Application Using CMOS 90nm Technology - Shankar, Gori; Gupta, Vijaydeep; Soni, Gaurav Kumar; Jain, Bharat Bhushan; Jangid, Pradeep Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2022)
WiFi is the innovation in wireless technology used to interface PCs, tablets, cell phones and different gadgets to the internet. The recent innovation WiFi works on two different frequency bands that bands are 2.4 GHz and 5 GHz. For larger coverage 2.4GHz frequency band is used and for higher data rate 5GHz frequency band is used. In this paper present the CMOS based operational transconductance amplifier (OTA) for 2.4GHz and 5GHz both frequency band WiFi application. The proposed OTA is designed using the CMOS 90nm environment with cascade current mirror architecture. The frequency tuning of the proposed OTA is done by using the varying capacitor.